Giant renal leiomyoma: a case report and brief review of the literature - Andreoiu, Matei; Drachenberg, Darrel; MacMahon, Ross (Canadian Urological Association Journal, 2013)
We report on a very large renal leiomyoma in a man presenting with a 1-year history of lower back and flank pain and a rapidly growing abdominal mass. Since a cystic renal cell carcinoma could not be ruled out, a postembolization right radical nephrectomy was performed. Diagnosis was confirmed by pathologic and histologic analysis. Renal leiomyomas are very rare benign tumours that are nearly indistinguishable from leiomyosarcoma or renal cell carcinoma preoperatively. This case represents the second largest such entity reported and demonstrates the limited ability of accurate diagnostic determination preoperatively, with pathologic examination and immune-histochemical staining postnephrectomy representing the only definitive means of diagnosis. A brief review of the literature and an outline of typical clinical and pathologic features of renal leiomyomas are also presented.